Practices and principles : approaches to ethical and legal judgment - Tunick, Mark (Princeton University Press, 1998)
In Practices and Principles, Mark Tunick takes up the debate between universalists and relativists, and, in political philosophy, between communitarians and liberals, each of which has roots in an earlier debate between Kant and Hegel.